Asymmetric Wealth Effect in the U.S and European Markets: Threshold Cointegration Approach - Pedro M. S. COELHO; Luís M. P. GOMES; Patrícia A. G. RAMOS (Communications of International Proceedings, 2021)
Evidence of the asymmetric wealth effect leads to significant implications for the portfolio managers. They have been seeking for markets with imperfect correlation, but the scientific results still present mixed empirical evidence. This problem justifies our research. This study aims to identify adjustment relationships from 1989 to 2020 between the American stock indexes – Standard and Poors 500 and Dow Jones Industrial Average, and the European stock indexes – Financial TSE 100 and Euro STOXX 50. Given that adjustments are different when negative and positive shocks occur, the Threshold Autoregression model and the Momentum Threshold Autoregression model were used to test the long-term equilibrium between those markets. In general terms, the results seem to support a long-term asymmetric cointegration among the SPX/FTSE, SPX/STOXX and DJIA/FTSE pairs of indexes, revealing a threshold effect.
Keywords: Threshold Autoregression; Momentum Threshold Autoregression; Cointegration; Asymmetric Error Correction; Financial Markets